Shopee Affiliate Program: Analysis of Influencer Content Marketing Strategy on Instagram - Cindhy Nurkolifah Siti Ariani; Rina Suthia Hayu (SIMAK, 2023)
The aim of this research is to analyze influencer content marketing strategies that utilize Instagram in the Shopee affiliate program. The type of research used is qualitative with a content analysis approach. Primary data was obtained directly from observations of phenomena and interviews with research subjects. Meanwhile, secondary data was obtained from the results of researchers' literature studies by collecting data from books, the internet and journals related to the research topic. The research results show that the influencer content marketing strategy on Instagram is an effective method for promoting and carrying out Shopee Affiliate Program activities. Support from influencers who apply stealth marketing techniques, both nano-influencers and macro-influencers are able to create interesting and persuasive content which can actually increase the attractiveness of the products being advertised.